Comparison of the effectiveness of exposure and response prevention (ERP) with mindfulness-based cognitive-behavioral therapy (MBCBT) on obsessive-compulsive syndrome and depression in women with obsessive-compulsive disorder - Elham Mohammadnejad; Farnaz Keshavarzi Arshadi; Fariba Hasani (مجله علوم روانشناختی, 2022)
Background: Various studies have investigated the effectiveness of Exposure and Response Prevention (ERP) on obsessive-compulsive disorder and depression, but few studies have examined ERP in a competitive trial with other methods such as mindfulness-based cognitive-behavioral therapy (MBCBT). Aims: The purpose of this study was to compare the effectiveness of two methods of mindfulness-based cognitive-behavioral therapy (MBCBT) and Exposure and Response Prevention (ERP) on obsessive-compulsive disorder and comorbid depression in women with obsessive-compulsive disorder. Methods: This study was designed as an “applied and quasi-experimental research” with pretest-posttest and follow-up design with two experimental groups 1 and 2 and control group. The statistical population in this study included all women in the age group of 20 to 45 years who referred to Amina and Rayen Psychological Services and Counseling Center in Tehran in 2018, 36 of whom were selected through purposeful sampling and were divided into three groups: 1) MBCBT group (n = 12), ERP group (n = 12) and control group (n = 12). Research tools included the Yale Brown Obsessive-Compulsive Disorder Questionnaire (Goodman, 1986) and the Beck Depression Inventory 2 (Beck, 1979). Data analysis was performed using repeated measures analysis of variance test by SPSS-21 software Results: In the post-test phase, both interventions had a significant effect on obsessive-compulsive disorder and depression (p >0.05). In the follow-up phase, two interventions significantly reduced obsessive-compulsive disorder and depression, but MBCBT was more effective. Conclusion: Based on the findings of this study, it can be concluded that MBCBT and ERP can be used to reduce the rate of obsessive-compulsive disorder and depression in women with obsessive-compulsive disorder.